2022
DOI: 10.1093/pcp/pcac164
|View full text |Cite
|
Sign up to set email alerts
|

TwoO-Methyltransferases from Phylogenetically Unrelated Cow Parsley (Anthriscus sylvestris) and Hinoki-Asunaro (Thujopsis dolabratavar.hondae) as a Signature of Lineage-Specific Evolution in Lignan Biosynthesis

Abstract: O-Methyltransferases (OMTs) play important roles in antitumor lignan biosynthesis. To date, six OMTs catalyzing the methylation of dibenzylbutyrolactone lignans as biosynthetic precursors of antitumor lignans have been identified. However, there is still no systematic understanding of the diversity and regularity of the biosynthetic mechanisms among various plant lineages. Herein, we report the characterization of two OMTs from Anthriscus sylvestris and Thujopsis dolabrata var. hondae [designated as AsSecoNorY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Researchers have already reported that Alpinia galanga extract leads to proteasome activation [24]. As for Thujopsis dolabrata leaf extract, the plant belongs to Cupressaceae family and is known to contain lignans [34], and it is reasonable that its extract had a positive effect. As for Hamamelis virginiana leaf extract, its similarity to JBE is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have already reported that Alpinia galanga extract leads to proteasome activation [24]. As for Thujopsis dolabrata leaf extract, the plant belongs to Cupressaceae family and is known to contain lignans [34], and it is reasonable that its extract had a positive effect. As for Hamamelis virginiana leaf extract, its similarity to JBE is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…2 , Table 2 ). From these plants, there are three distinct OMTs that have been identified to catalyze methylation at the same position of their substrate lignans ( Lau and Sattely 2015 , Yamamura et al. 2023 ).…”
Section: Catalytic Convergence In Enzymesmentioning
confidence: 99%
“…OMTs in plants typically act on compounds containing phenolic hydroxyl groups, such as phenylpropanoids, avonoids, and alkaloids, to methylate their oxygen atoms 27,28 . They are a crucial regulatory enzyme in the phenylpropanoid metabolic pathway, which is derived from the shikimate pathway 29 . Pinane, the common precursor of podophyllotoxin, is one of the important natural secondary metabolites in the phenylpropanoid metabolic pathway of plants 30 .…”
Section: Introductionmentioning
confidence: 99%